2020
DOI: 10.3390/microorganisms8030316
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Polymorphism and Copy Number Variation of mtSSU rDNA in Ciliates (Protista, Ciliophora): Implications for Phylogenetic, Environmental, and Ecological Research

Abstract: While nuclear small subunit ribosomal DNA (nSSU rDNA) is the most commonly-used gene marker in studying phylogeny, ecology, abundance, and biodiversity of microbial eukaryotes, mitochondrial small subunit ribosomal DNA (mtSSU rDNA) provides an alternative. Recently, both copy number variation and sequence variation of nSSU rDNA have been demonstrated for diverse organisms, which can contribute to misinterpretation of microbiome data. Given this, we explore patterns for mtSSU rDNA among 13 selected ciliates (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Recent faunistic studies have revealed numerous new taxa of hypotrichous ciliates suggesting that this group is more diverse than previously supposed [1][2][3][4][5][6][7][8]. Furthermore, much work has been carried out on the morphogenesis and molecular phylogeny of hypotrichs, which has led to a better understanding of their systematics and evolutionary relationships [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent faunistic studies have revealed numerous new taxa of hypotrichous ciliates suggesting that this group is more diverse than previously supposed [1][2][3][4][5][6][7][8]. Furthermore, much work has been carried out on the morphogenesis and molecular phylogeny of hypotrichs, which has led to a better understanding of their systematics and evolutionary relationships [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As predators, producers, decomposer, and parasites, microeukaryotes represent the bulk of microbial diversity and play key roles in the ecological functioning and process of aquatic biological ecosystems ( Bik et al, 2012 ; Zhang et al, 2018 ; Zhao et al, 2018 ; Chen X. et al, 2019 ; Chi et al, 2019 ; Lu et al, 2019 ; Wang et al, 2020 ; Xu et al, 2020 ). Previous studies showed that several environmental factors play important roles in structuring microeukaryotic communities on biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Ciliates (phylum Ciliophora Doflein, 1901), a highly diverse and ubiquitously distributed group of unicellular microbial eukaryotes, play substantial roles in various ecosystems. A lot of attention has been therefore paid to their diversity, function and evolution (e.g., Bharti et al, 2019;Hu et al, 2019;Jung and Berger, 2019;Kaur et al, 2019;Luo et al, 2019;Wang et al, 2019;Yan et al, 2019;Gong et al, 2020;Shao et al, 2020;Sheng et al, 2020;Wang Y. R. et al, 2020;Zhang et al, 2020). Hypotrichs (subclass Hypotrichia Stein, 1859) are not only among the most differentiated ciliate groups, but also among the most confused ones in terms of their systematics and phylogeny (for reviews, see Berger, 1999Berger, , 2006Berger, , 2008Berger, , 2011Luo et al, 2017;Song and Shao, 2017;Luo et al, 2018;Lyu et al, 2018;Kim and Min, 2019;Chen et al, 2020;Dong et al, 2020;Paiva, 2020;Park et al, 2020;Wang J. et al, 2020;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%